Updating information in colored QR code for knowledge sharing - Abas, Azizi; Yusof, Yuhanis; Ahmad, Farzana Kabir (2016)
Knowledge sharing is the process through which explicit or tacit knowledge is communicated to other individuals.Recently, the Quick Response (QR) Code which is a small size printed shape of black and white squares has been used in many domain as a storage medium.To date, it is a popular storage medium in the marketing domain. The code can easily be used to disseminate information about a product as it only requires a small printed area.The QR Code may contain various information such as URL, contact information, and application launching. However, the information stored in the QR Codes may require some modification or updating. Hence, this paper demonstrates a technique to update information stored in colored QR Code and regenerate the code using integrated techniques of compression, multiplexing and multilayered techniques (CoMM). The processes to regenerate an updated QR Code includes the decode and re-encode of the QR Code.